DAMPAK PENERAPAN APLIKASI E-PROCUREMENT DALAM MENINGKATKAN TRANSPARANSI PENGADAAN BARANG DAN JASA PADA KANTOR LEMBAGA PENDIDIKAN ISLAM - YUSUF, M. (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2024)
The procurement of goods and services in educational offices plays a vital role in supporting operational sustainability. This article discusses the impact of implementing e-procurement applications in enhancing transparency in the procurement process within the education sector. The research background reflects the complexity and challenges of conventional procurement systems. Using a library research method, this article explores literature related to the implementation of e-procurement in improving efficiency and transparency. The formulation of the problem focuses on the constraints in conventional procurement that can be addressed by e-procurement. The research objective is to analyze the impact of the application on the transparency and effectiveness of procurement. The research results indicate that e-procurement accelerates the process, reduces costs, and enhances clarity throughout the procurement cycle. Thus, the implementation of e-procurement can significantly contribute to improving the transparency of goods and services procurement in educational offices.